Comparison of the influence of light between circularly polarized and linearly polarized smartphones on dry eye symptoms and asthenopia. Issue 4 (27th December 2021) - Mou, Yujie; Shen, Xiao; Yuan, Kelan; Wang, Xin; Fan, Fangli; Wu, Yaying; Wang, Chunyang; Jin, Xiuming
Abstract: This paper aims to investigate the efficacy of circularly polarized light smartphones in affecting dry eye symptoms and asthenopia through a comparison with linearly polarized smartphones. One hundred twenty participants were randomly divided into four groups. Dry eye and asthenopia symptoms were evaluated using the Ocular Surface Disease Index (OSDI), Computer Vision Syndrome Scale 17 (CVSS17), Convergence Insufficiency Symptom Survey (CISS), and visual analogue scale (VAS). Objective ocular examinations were assessed by confusion flicker frequency (CFF), tear meniscus height (TMH), noninvasive break‐up time (NIBUT), conjunctiva redness, fluorescein tear break‐up time (FTBUT), corneal fluorescein staining, and the Schirmer I test. Tests were performed before and after a reading task. Subjective evaluations including the OSDI, CVSS17, and CISS were all significantly increased after reading on a linearly polarized smartphone, whereas no change was observed in the circular polarization groups in both light and dark environments. A significantly enlarged VAS was shown in all of the four groups, but a significant increase in ΔVAS only appeared in the linear polarization groups. There were significant decreases in TMH, NIBUT, conjunctiva redness, FTBUT, and CFF after reading on a linearly polarized smartphone but the circularly polarized smartphone had lesser effects on these parameters. Our study indicated that reading on linearly polarized smartphones may cause dry eye disorder, asthenopia, and ocular discomforts, whereas circularly polarized smartphones appears to minimize these adverse effects on eye dryness and visual fatigue in light and dark environments.